Performance assessment approach based on change-point detection for network moving target defense - Cheng LEI; Duo-he MA; Hong-qi ZHANG; Ying-jie YANG; Miao WANG (Tongxin xuebao)
A performance assessment approach based on change-point detection for network moving target defence was proposed.Directed to the problem of network resource graph not being able to present the effect of network resource vulnerabilities to network nodes,a conversion relationship between resource vulnerability changes and node security states was established by defining the concept of a hierarchical network resource graph and the efficiency of resource graph construction and updating were improved.Furthermore,directed to the problem of static detection algorithm not being able to precisely measure the dynamic change of network moving target defense,a change-point detection algorithm and standard degree measurement algorithm was designed.The security cost and benefit of network moving target defense in real-time and dynamically on the basis of unified metrics were defected and measured,which improved the evaluation accuracy.The analysis result of typical examples has proved the feasibility and the effectiveness of the proposed approach.